2019
DOI: 10.3389/fvets.2019.00336
|View full text |Cite
|
Sign up to set email alerts
|

Animal Welfare and the United Nations Sustainable Development Goals

Abstract: This paper systematically evaluates the extent to which achieving the UN sustainable development goals (SDGs) is compatible with improving animal welfare. The analyses were based on discussion and independent scoring in a group of 12 participants with academic backgrounds within agricultural or veterinary sciences. We considered all categories of animals; those kept for food production, working and companion animals, but also laboratory and wild animals. The strengths of the links between improving animal welf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 18 publications
1
70
0
2
Order By: Relevance
“…A workshop called "Animal Welfare and the Sustainable Development Goals" in 2018 at the Swedish University of Agricultural Science had a group of 12 active participants, from eight countries, with an academic background in agricultural or veterinary science. They evaluated every goal and found that although animal welfare was not explicitly mentioned in the SDGs, working to achieve those goals is compatible with working the improvement of animal welfare [170].…”
Section: Consequences Of Human-animal Relations For the Environmentmentioning
confidence: 99%
“…A workshop called "Animal Welfare and the Sustainable Development Goals" in 2018 at the Swedish University of Agricultural Science had a group of 12 active participants, from eight countries, with an academic background in agricultural or veterinary science. They evaluated every goal and found that although animal welfare was not explicitly mentioned in the SDGs, working to achieve those goals is compatible with working the improvement of animal welfare [170].…”
Section: Consequences Of Human-animal Relations For the Environmentmentioning
confidence: 99%
“…At first glance, animal welfare only applies to Goal 2 though even here it is not explicitly mentioned. However, a deeper examination of the SDG agenda revealed that out of 169 targets, 66 are relevant to animal welfare (145). More importantly, relationships between the SDGs and animal welfare were all positive, such that there was no situation where attainment of the SDG conflicted with improving or safeguarding animal welfare (145).…”
Section: Long Term System Overhaulmentioning
confidence: 99%
“…There are substantial barriers to implementing animal control policies that promote One Health and One Welfare, including inherent biases regarding how and why individuals living in poverty may require additional support resources (e.g., they are just “lazy” and need to get a job so they can pay for their pet’s care on their own, rather than relying on government handouts); the animal welfare field’s historic commitment to a specific definition of “responsible pet ownership” that is driven by racism, classism, and the White dominant culture; an absence of strategies for engaging with marginalized populations in a culturally competent manner; over-policing in communities of color; lack of transparency and oversight in data regarding enforcement; lack of a concerted effort to address structural barriers to accessing pet support services; lack of animal control officer training to perform basic animal handling and zoonoses prevention tasks or in de-escalation strategies; and limited funding opportunities for projects aimed at achieving One Health and One Welfare outcomes [ 4 , 5 , 25 , 26 , 27 , 28 , 29 , 30 ]. Without identifying specific strategies for overcoming each of these barriers, the implicit bias that is present in animal control policy will continue, resulting in disproportionately negative impacts on the pet owners of color and their pets that live in low-income communities.…”
Section: One Health and One Welfare In Animal Control Reformmentioning
confidence: 99%